Arrhythmogenic Substrates for Atrial Fibrillation in Obesity - Lubbers, Ellen R.; Price, Morgan V.; Mohler, Peter J. (Frontiers in Physiology, 2018)
Global obesity rates have nearly tripled since 1975. This obesity rate increase is mirrored by increases in atrial fibrillation (AF) that now impacts nearly 10% of Americans over the age of 65. Numerous epidemiologic studies have linked incidence of AF and obesity and other obesity-related diseases, including hypertension and diabetes. Due to the wealth of epidemiologic data linking AF with obesity-related disease, mechanisms of AF pathogenesis in the context of obesity are an area of ongoing investigation. However, progress has been somewhat slowed by the complex phenotype of obesity; separating the effects of obesity from those of related sequelae is problematic. While the initiation of pathogenic pathways leading to AF varies with disease (including increased glycosylation in diabetes, increased renin angiotensin aldosterone system activation in hypertension, atrial ischemia in coronary artery disease and sleep apnea) the pathogenesis of AF is united by shared mediators of altered conduction in the atria. We suggest focusing on these downstream mediators of AF in obesity is likely to yield more broadly applicable data. In the context of obesity, AF is driven by the interrelated processes of inflammation, atrial remodeling, and oxidative stress. Obesity is characterized by a constant low-grade inflammation that leads to increased expression of pro-inflammatory cytokines. These cytokines contribute to changes in cardiomyocyte excitability. Atrial structural remodeling, including fibrosis, enlargement, and fatty infiltration is a prominent feature of AF and contributes to the altered conduction. Finally, obesity impacts oxidative stress. Within the cardiomyocyte, oxidative stress is increased through both increased production of reactive oxygen species and by downregulation of scavenging enzymes. This increased oxidative stress modulates of cardiomyocyte excitability, increasing susceptibility to AF. Although the initiating insults vary, inflammation, atrial remodeling, and oxidative stress are conserved mechanisms in the pathophysiology of AF in the obese patients. In this review, we highlight mechanisms that have been shown to be relevant in the pathogenesis of AF across obesity-related disease.